Analisis Faktor Determinan Keluhan Work-Related Musculoskeletal Disorder pada Karyawan Bagian Teknisi dan Operator di Perusahaan Gas Negara Solution Area Lampung - Reandy Ilham Andriyono; Fitria Saftarina; Minerva Nadia Putri; Dewi Nur Fiana (Majority, 2021)
Musculoskeletal disorders (MSDs) are biggest complaints felt by employees and have several risk factors are biomechanical factors, individual factors, and psychosocial factors. MSDs can affect the performance of an employee. Determine the determinant factors of the Work-Related Musculoskeletal Disorder (WMSDs) complaints on technician and operator employees at Perusahaan Gas Negara Solution Area Lampung. The research method used a cross sectional with total sampling technique that included inclusion criteria. Respondents were analyzed using Rapid Entering Body Assessment (REBA) scoring and measured their height and weight, and filled questionnaires are Self Biodata, Copenhagen Psychosocial Questionnaire II (CopSoq II), and Nordic Body Map (NBM). The results of univariate analysis on various factors were obtained namely age (100% of adult category employees), length of work (56% of employees working category> 8 hours), length of service (66% of employees entered the category> 3 years and 40% entered the category ≤3 years ), smoking habits (74% of employees have smoking habits), body mass index (62% of employees including fat category), work posture (100% of employees in the low category), psychosocial (52% of employees including good category and 48% bad, WMSDs (70% of employees have complaints and 30% of employees have no complaints). Based on bivariate analysis with Chi square test (p